Indigenous Knowledge Production Navigating Humanity within a Western World - Woolombi Waters, Marcus (2018)
Despite many scholars noting the interdisciplinary approach of Aboriginal knowledge production as a methodology within a broad range of subjects - including quantum mathematics, biodiversity, sociology and the humanities - the academic study of Indigenous knowledge and people is struggling to become interdisciplinary in its approach and move beyond its current label of 'Indigenous Studies'. Indigenous Knowledge Production specifically demonstrates the use of autobiographical ethnicity as a methodological approach, where the writer draws on lived experience and ethnic background towards creative and academic writing. Indeed, in this insightful volume, Marcus Woolombi Waters investigates the historical connection and continuity that have led to the present state of hostility witnessed in race relations around the world; seeking to further one's understanding of the motives and methods that have led to a rise in white supremacy associated with ultra-conservatism. Above all, Indigenous Knowledge Production aims to deconstruct the cultural lens applied within the West which denies the true reflection of Aboriginal and Black consciousness, and leads to the open hostility witnessed across the world. This monograph will appeal to undergraduate and postgraduate students, as well as postdoctoral researchers, interested in fields such as Sociology of Knowledge, Anthropology, Cultural Studies, Ethnography and Methodology.